Exploring Science Attitudes, Misconceptions, and Temperature Correlations: Menjelajahi Sikap Sains, Miskonsepsi, dan Korelasi Suhu - Alfania Citra, Aulia; Shofiyah, Noly (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates junior high school students' attitudes towards science and their misconceptions regarding temperature changes, aiming to understand the relationship between these two factors. Conducted at SMP Muhammadiyah 6 Krian with 93 seventh-grade students, the research utilizes non-experimental quantitative methods, including questionnaires and statistical analyses. Findings reveal that while students exhibit generally positive attitudes towards scientific investigation, misconceptions about temperature changes are low. However, the correlation between students' attitudes towards science and their misconceptions is observed to be low. These results underscore the importance of addressing both attitudes and misconceptions in science education to optimize learning outcomes.Highlight: Investigates student attitudes and misconceptions about temperature changes in science. Positive attitudes but low misconceptions found in junior high students. Correlation between attitudes and misconceptions in science education explored. Keywoard: Attitudes Towards Science, Misconceptions, Temperature Changes, Junior High School Students, Science Education